Nickel nanoparticles inlaid in lignin-derived carbon as high effective catalyst for lignin depolymerization. (October 2019) - Wang, Da; Li, Guangci; Zhang, Chuanhui; Wang, Zhong; Li, Xuebing
Highlights: Lignin could be effectively converted into bio-oil over inlaid type Ni/C-R catalyst. The Ni/C-R catalyst has high stability for lignin depolymerization. The Ni/C-R catalyst has unique electron structure. Mechanism studies show that the Ni/C-R has better bond breaking ability. Abstract: Ni nanoparticles inlaid in lignin-derived carbon constructing the "inlaid type" Ni/C-I was reported to improve stability and adjust metal-support interaction of lignin hydrogenolysis catalyst. The Ni/C-I was further heat treated in air to prepare Ni/C-R so as to re-expose the blocked active sites by carbon species. A lot of characterization techniques were carried out to confirm the "inlaid structure" of the catalysts. The lignin depolymerization results demonstrated that the Ni/C-R had better catalytic performance than traditional "supported type" Ni/C, 23.3% aromatic monomer yield and 82.4% bio-oil yield were achieved. Moreover, the mechanism studies with lignin model compound revealed that Ni/C-R had better bond breaking ability than Ni/C, even CC bond could be cleaved. The electron effect could be responsible for that, since the electrons could transfer from Ni 0 to carbon support for Ni/C-R, which could improve the bond breaking ability.